Controle de Meloidogyne incógnita em tomateiro com resíduo orgânico, fungos nematófagos e material quitinoso - Mendonça, Valdenia Cristina Mendes (2005)
The root-knot nematodes {Meloidogyne ssp.) they are among the most noxious enemies of the plants cultívated all o ver the world. The incorporation of organic matter, the use of rich materiais in chitin and the biological control wíth fungus nematodes-destroying, they come blunting as promising altematives in the control of the nematodes. This work had as objective to evaluate the effects ofthe incorporation of the organic residue of fava d’anta tree {Dimorphandra gardneriana Tul.), material chitinous and fungus nematodes-destroying, alone or in combination, on Meloidogyne incógnita race 1 in tomato plant. Five experíments were accomplished, where the first proceeded a completed randomized experimental desing, with the following: soil (control), soil: fava d’anta tree, in the proportions treatments 2:1, 1:1 e 1:2, without and with inoculation (5.000 eggs of Meloidogyne / vase), with six repetitions. In the second experiment, the used treatments were the following ones: soil (control); substrate (soil + fava d’anta tree), soil + crab waste; soil + oyster flour; soil + Anomalocardia brasiliana G. whitewash; substrate + crab waste; subatrate + oyster flour; substrate + Anomalocardia brasiliana G. whitewash. A completely randomized experimental design was adopted with six repetitions. In the third experiment, it was also completely randomized experimental design, with treatments arranged in a 3x3 factorial and six replicated. Three incubation periods (0, 15 and 30 days) ofthe eggs of M incógnita race 1 and ofthe crab waste, and three diíferent proportions of crab waste (0, 5 and 10 g). In the fourth experiment, it was completely randomized experimental design with with 7 repetitions, and the